MTHFR 677C/T gene polymorphism and dietary habits: effects on trace element levels, amino acids, and biochemical parameters - Orct, Tatjana; Kovačić, Jelena; Peremin, Ines; Kljaković-Gašpić, Zorana; Pašalić, Daria; Sekovanić, Ankica; Dorotić, Adrijana; Tariba Lovaković, Blanka; Jurič, Andreja; Pizent, Alica; Crnjac, Fran; Dukić, Lora; et al. (Frontiers in Nutrition, 2026)
BackgroundPrevious research has identified that, in individuals with lower folate and/or vitamin B12 levels, homocysteine is associated with specific elements, while amino acids are associated with folate, thereby influencing folate availability during supplementation. This study investigates the impact of the MTHFR 677C/T polymorphism on levels of these compounds in individuals with differing meat consumption preferences, non-vegetarians and vegetarians.MethodsThe study was conducted on 162 Croatian subjects. MTHFR gene polymorphism was determined by PCR-RFLP, elements by ICP-QQQ, amino acids by GC–MS, and biochemical parameters by chemiluminescent immunoassay and enzymatic methods. Differences between the groups were tested by ANOVA, while associations between the parameters were examined by multiple regression analyses.ResultsThe CT + TT genotype had lower folate levels in comparison to the CC genotype. The influence of MTHFR 677C/T polymorphism on element levels was limited to Al and Ca: individuals with the CT + TT genotype exhibited higher plasma Ca levels than the wild-type (CC) genotype, while lower plasma Al values were observed only in vegetarians with the CT + TT genotype. The CT + TT genotype was also associated with higher levels of glutamic acid, proline, glycine (only in vegetarians), and aspartic acid.ConclusionAlthough we observed an effect of the MTHFR 677C/T polymorphism on folate, certain elements and amino acid levels, further research is required to validate our findings and establish a more comprehensive understanding of the link between elements, amino acids and the MTHFR gene polymorphism.